PENGARUH PENERAPAN ALGORITMA TERHADAP PEMBELAJARAN PEMROGRAMAN KOMPUTER - Mahmud S, Ronald; Nazaruddin, Ilham; Mardianto, Mardianto; Nasution, Ibnu Hajar; Syahputra, Angga (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
The advancement of information and computer technology is currently increasingly advanced, all fields of science require computer skills, so for students an understanding of mathematical logic and computer learning is very important because the two are interrelated. Based on the experience of learning computer programming courses, there are still many students who have not mastered the course. To overcome this, research was conducted by applying mathematics in computer programming learning. This research can be a qualitative research that aims to see the effect of the application of mathematics on student learning outcomes in computer programming learning. The research sample was students of STKIP AMAL BAKTI Medan in the 2024/2025 academic year consisting of two classes (experimental class and control class). After conducting the research, the following results were obtained: 1) The learning outcomes of students after applying mathematics to each programming class were better than students who received normal learning in terms of students in general; 2) The learning outcomes of students after applying calculations to each program structure were much better than students who received normal learning in terms of KAM (high, medium, and young)